Scrutinizing Learner Variability in English Language Teaching Classes - Neupane, Nabaraj (Journal of NELTA Gandaki, 2025)
Learners are at the centre of concentric rings of the pedagogical spheres. They are not only individuals but also vital members of the communities they come from. In the meta-modern world, mixed communities in terms of race, ethnicity, culture, educational background, and language have been common. This context leads to a heterogeneous group of learners in the classrooms, including English language teaching (ELT) classes. Thus, learner variability is a common currency of the research arena. This article explores the determinants of learner variability that have resulted in diversity in ELT classes. Employing a document analysis method, the contents from the available documents have been critically analyzed to infer the variables of the phenomenon in question. The findings demonstrate the intricacy of biological, psychological, physiological, and social variables that have enforced the facilitators to adapt multi-pronged pedagogical approaches. These variables explored in ELT classes exhibit age, aptitude, motivation, personality, style, affect, and strategy from the prism of learner variability. These findings imply that educators should be aware of learner variability for fostering a congenial and equitable atmosphere for all learners in ELT classes.